PENGARUH PENGUASAAN DIKSI DAN GAYA BAHASA TERHADAP KETERAMPILAM MENULIS NASKAH PIDATO OLEH SISWA KELAS XI SMA NEGERI 1 BATANGTORU - Padilah, Hikmah; Hasibuan, Nikmah Sari; Daulay, Ismail Rahmad (Linguistik : Jurnal Bahasa dan Sastra, 2024)
Abstract: The purpose of this study was to determine the effect of using the learning discovery learning model on the ability toidentify the structure of anecdote text for class X students of SMA Negeri 1 Padang Bolak Julu. This research method uses quantitative methods with a descriptive approach. The population in this study were all students of class X SMA Negeri 1 Batang Toru, totaling 167 students. The sample used in this study were 26 students of class X IPA2 at SMA Negeri 1 Batang Toru consisting of 10 boys and 16 girls. The sample was determined using a purposive sampling technique. The data collection technique uses a test in which this test uses 10 multiple choice questions and 5 filled-in question. The results of the study show the difference in the average value of the X and Y variables. The average value of the X variable is 79,61 "Good" while the value on the Y variable test results is 78,46 in the "Good" category. After the data is analyzed, it can be stated that N = 26 with X = 2070, Y = 2040, X2 = 166100, Y2 = 161700, so XY = 163650. This is based on the hypothesis testing carried out on the data found, namely the hypothesis obtained that the value of rxy is 0,84 so when compared with the r table, namely (0,84 0,38) then the hypothesis in this study is accepted.